Transesterification of alpha-haloesters and beta-ketoesters over Mg-Al-hydrotalcites (HT)-like anionic clays - Bulbule, Vivek J.; Borate, Hanumant B.; Munot, Yogesh S.; Deshpande, Vishnu H.; Sawargave, Sangmeshwer P.; Gaikwad, Abaji G. (Journal of Molecular Catalysis A-Chemical, 2007)
Transesterification of alpha-haloesters was achieved by reaction of alcohols in the presence of Mg-Al-HT-like anionic clays. beta-Ketoesters were also transesterified under similar conditions on reaction with alcohols with a wide variety of functional groups. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alpha-haloesters; beta-ketoesters; heterogeneous catalyst; Hydrotalcites; transesterification